PENGEMBANGAN VIDEO PEMBELAJARAN HAK DAN KEWAJIBAN WARGA NEGARA BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X E.3 SMA PGRI 2 KOTA - Yuni Oktaviarani; Hendra; Ridwan Santoso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information technology has encouraged innovation in learning media to improve students' learning outcomes. This study aimed to develop Canva-based learning videos on the topic of rights and obligations as school and community members and to determine the validity, practicality, and effectiveness of the developed media. This study employed a Research and Development (R&D) approach using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The research subjects involved material experts, media experts, teachers, and students of class X E.3 SMA PGRI 2 Jambi City. Data were collected through observation, interviews, questionnaires, and learning achievement tests. Data were analyzed descriptively using quantitative and qualitative approaches. The results showed that the material expert validation obtained a score of 92.5% categorized as very feasible. The practicality test indicated that the media was categorized as practical to very practical based on teacher and student responses. The effectiveness test using the Wilcoxon Signed Rank Test showed a significance value of 0.001 (<0.05), indicating a significant difference between pre-test and post-test scores. Furthermore, Cohen's r value of 0.885 indicated a large effect size. Therefore, Canva-based learning videos are valid, practical, and effective for improving students' learning outcomes.